Performance-based contracts for road projects : Comparative analysis of different types - Gajurel, Ashish (Springer India, 2014)
This book focuses on the aspects of contracting contracts, basically related to road construction and management contracts. The book presents an analytical study of Performance-Based Road Management and Maintenance (PMMR), Funktionsbauvertrag (FBV) (Function-Based Construction Contract) and Public Private Partnerships (PPP). A separate chapter is also included about the comparative study of these contract types. The book provides useful material for university libraries, construction companies and government departments of construction.